The National Road and the Difficult Path to Sustainable National Investment. - Sky, Theodore (Rowman & Littlefield Pub. Group, 2011)
The National Road is a comprehensive history of the first federally financed interstate highway, an approximately 600-mile span that joined Maryland, Pennsylvania, West Virginia, Ohio, Indiana, and Illinois in the nineteenth century. This book covers the road's contribution to the cultural, economic, and administrative history of the United States, its decline during the second half of the nineteenth century, and its revival in the twentieth century in the form of U.S. Route 40. The story of the National Road embraces an account of its building, its constitutional significance, the unique cul.